Market Segmentation Analysis of Non-Mental Outpatient Health Services at Menur Mental Hospital East Java Province: Analisis Segmentasi Pasar Pelayanan Kesehatan Rawat Jalan Non Jiwa di Rumah Sakit Jiwa Menur Provinsi Jawa Timur - Yasmine Alisha Tari Syahputri; Anif Prasetyorini (Bachelor of Hospital Administration, Faculty of Health Sciences, Universitas Singaperbangsa Karawang, 2024)
Introduction: The increasing number of new hospital growth can trigger competition between hospitals. Market segmentation needs to be done with the aim of marketing can be done optimally. Purpose of the study: to determine market segmentation based on the characteristics of health service users in the non-mental outpatient clinic of Menur Mental Hospital, East Java Province. Research Methods: This type of research is quantitative research with a cross sectional approach. The population was non-mental outpatients of Menur Mental Hospital, East Java Province, totaling 99 respondents. The sampling technique was purposive sampling. Data collection techniques using questionnaires. Data analysis using non-hierarchical cluster test. Research Results: shows that market segmentation in the non-life outpatient clinic of Menur Mental Hospital is divided into three segments. Segment I is hospital care maximizer, segment II is hospital care minimizer, segment III is hospital care aversion. Conclusion: Market segmentation at Menur Mental Hospital, East Java Province is grouped into three segments, namely hospital care maximizer, hospital care minimizer, and hospital care aversion.